Efektivitas Manajemen Dalam Revitalisasi Kuttab di Indonesia Pada Era Modern: Tinjauan Literatur Sistematis - Ulum, Fachrurizal Bachrul; Susanti, Linna; Nurhuda, Abid; Lathif, Nur Muhammad (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
At present, there is an effort to revitalize the function of kuttab in Indonesia through kuttab al Fatih.  This study aims to analyze the kuttab al Fatih curriculum, especially in the field of life skills education as an Islamic educational institution. This research is a type of library research with descriptive and analytical methods. Sources of data are taken through literature review from books, articles, and literature relevant to the topic of discussion. The analysis technique uses Miles and Huberman's, which consists of data reduction, data display, and conclusion drawing. This study concludes that there is a distinctiveness of the Kuttab al Fatih curriculum which is drawn from the Qur'an and Hadith as well as the books of salaf scholars.  The link to the main Islamic references is also seen in learning the life skills of its students. The study in this research can add insight into the urgency of the kuttab concept as an Islamic educational institution in Indonesia. This research produces new discussions about the types of general and specific skills taught in the learning process at kuttab al Fatih.